The Mechanical Properties of the Extra Hard Spring Arch Wire Subjected to the Artificial Saliva - Hussain A Obaidi; Sarmad S Al-Qassar (University of Mosul, College of Dentistry, 2009)
Aims: To evaluate and compare the value of the mechanical properties of the extra hard spring stainlesssteel arch wire immersed in artificial saliva. Materials and Methods: The sample consisted of 40extra hard spring stainless steel arch wires (Remanium, 0.016" × 0.016", Dentarum, Germany) dividedinto; control wires group and experimental group (ten wires for each group). The experimental groupwas immersed in artificial saliva (PH 6.75+ 0.015) ) and incubated at 37 for one, two and four weeksrespectively. The curve of tensile strength for the control and experimental groups was performed usingthe tensile testing machine. The mechanical properties of the arch wire have been derived. The resultswere analyzed using the statistics of descriptive, Anova and Duncan's Multiple Range Analysistests. Results: The results showed that the mechanical properties (ultimate tensile strength, elasticmodulus, springiness (springback) ,elastic limit, plastic limit (ductility) of the extra spring hard stainlesssteel arch wire significantly decrease as the immersion time in artificial saliva increase when comparedwith the control group. Conclusions: It is recommended not utilize the extra spring hard stainlesssteel arch wire for long periods during orthodontic treatments.